A senior Agri lady wearing a veil - Mumbai Archive Project Team (Jio Institute, 2024)
A senior Agri lady wears a veil over the traditional saree. The veil covers the entire upper body, including the neck, shoulders, and head, leaving only the face exposed. The veil was once prevalent among the Catholic community but is rarely worn now, except by the older generation.